Family union and health in the Aymara people - Salazar Recio, Inocencio (1972)
During the time that I have been in the parish of San Miguel de Ilave, I have had the opportunity to attend the religious acts of the Aymaras two or three times a month, for the space of nearly two years. With this experience I present these observations about the Aymara family, based on their religiosity. In my opinion, the lifestyle of the Aymara family creates the environment for the religion that is put into practice. In turn, the rites of this religion confirm or re-establish family ties; It is precisely through this family union that an individual enjoys health, prosperity, and, above all, social acceptance.